Un anno di bookface - Denunzio, Paola; D'Urso, Stefania (Fuori collana, 2022)
Behind the bookface, which at first may seem like an easy "photographic" operation, there is actually an intention of cultural communication aimed at both library users and all potential readers.The phenomenon, practiced by libraries all over the world, publishers and private users, has an incredible outcome, so much so that it has become a weekly appointment recognizable by the hashtag #bookfacefriday.